A complex roof incorporating phase change material for improving thermal comfort in a dedicated test cell. (February 2017) - Guichard, Stéphane; Miranville, Frédéric; Bigot, Dimitri; Malet-Damour, Bruno; Beddiar, Karim; Boyer, Harry
Abstract: The use of phase change materials (PCMs) as a building integrated thermal storage may contribute to improving building energy performances. This article focuses on the integration of PCMs in the roof with a non-ventilated air layer, in order to assess thermal performances of a dedicated test cell, especially for thermal comfort. An experimental equipment was set up at Reunion Island under tropical and humid climatic conditions. A mathematical model, based on the apparent heat capacity method is used to predict the actual impact of PCMs on energy consumption as well as thermal comfort. Once the comparisons are performed with simulations, the use of the psychrometric chart, Predicted Mean Vote and Predicted Percentage of Dissatisfied indexes, shows that in the tested configurations, thermal comfort can be improved. Indeed, as well as to enhance the thermal energy storage, the given configuration also reduce the solar radiation through the roof, due to the reflective properties of PCMs panel surfaces. A positive effect on inside air temperature of the full-scale experimental test cell is particularly observed. Highlights: Full-scale experimental investigation with PCM in the roofing complex. Validation of a numerical model of thermal behaviour of PCM with experimental data. Study of thermal comfort in field measurements from an experimental test cell. Evaluation of thermal comfort by both PPD and PMV indexes.